ISOLATION AND STUDY OF LACTIC ACID BACTERIA FROM MATSUN’S FERMENTS OF DIFFERENT REGIONS OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
Matsun samples from different regions of Armenia were collected. Lactic acid bacteria belonging to genus Lactobacillus and Streptococcus were isolated and studied. Their high antibacterial activity against gram-positive and gram-negative bacteria has been shown.
Keywords: $Lactobacillus$ and $Streptococcus$; antibacterial activity; matsun